2019
DOI: 10.1001/jamanetworkopen.2019.16091
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Percentage of Patients With Fibroblast Growth Factor Receptor Alterations Eligible for Off-label Use of Erdafitinib

Abstract: IMPORTANCE When a novel drug is granted accelerated approval, both its on-label and off-label uses must be taken into account. OBJECTIVES To estimate the potential upper bound of off-label use of erdafitinib to treat advanced cancer with fibroblast growth factor receptor gene (FGFR) alterations, compare it to the upper bound of on-label use in urothelial cancer, and to review studies that may support off-label use. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study used frequency data on FGFR alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
(60 reference statements)
1
13
0
2
Order By: Relevance
“…Moreover, erdafitinib is limited to patients with FGFR2/3 mutation or fusion (15%-20% of patients depending on cancer type). 11 Hence, new agents are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, erdafitinib is limited to patients with FGFR2/3 mutation or fusion (15%-20% of patients depending on cancer type). 11 Hence, new agents are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…This study led to the approval of erdafitinib for second-line advanced urothelial cancer patients with FGFR2/3 alterations ( 20 ). A subsequent study estimated the off-label use of several drugs, including erdafitinib and determined that the potential off-label erdafitinib users could be up to 3 times greater than under the current recommendations ( 21 ). On the other hand, infigratinib is a potent FGFR1-3 inhibitor with demonstrated single-agent antitumor activity in FGFR3 mutant early-stage urothelial cancer patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, refinement of molecular techniques for the design of target-specific molecules and careful selection of patients have demonstrated the potential benefit of FGFR blockade in the growing portfolio of cancer drugs, especially in tumors with poor survival, such as cholangiocarcinoma [44]. A recent study showed that among patients with tumors driven by FGFR aberrations, 76% would be considered ineligible for target therapy due to currently approved indications, comprising 15 different tumor types, potentially susceptible to therapy with TKIs [45].…”
Section: A Pharmacological Overview On the Anti-fgfr Agentsmentioning
confidence: 99%